Strategi Kreatif Guru dalam Penggunaan Kartu Gambar pada Kemampuan Bahasa Anak Usia Dini - Suhailah Abnan; Syamsyiah Depalina (Jurnal Pendidikan Bahasa dan Anak Usia Dini, 2025)
Language ability is a crucial foundation for early childhood development. During this period, children are actively building vocabulary, understanding sentence structure, and learning to communicate effectively. This research is a library study, taking its research object from books that reinforce the theory that picture card media can improve early reading ability in young children. One of the most effective and easy-to-use tools for teachers to stimulate language skills is picture cards. Their use is not merely showing pictures and naming them, but also requires creative strategies to make learning more enjoyable and meaningful. The purpose of this article is to find out how teachers use strategies to improve early childhood language skills.